Safety and tolerability of antipsychotic co-treatment in patients with schizophrenia: results from a systematic review and meta-analysis of randomized controlled trials. Issue 5 (3rd May 2016) - Galling, Britta; Roldán, Alexandra; Rietschel, Liz; Hagi, Katsuhiko; Walyzada, Frozan; Zheng, Wei; Cao, Xiao-Lan; Xiang, Yu-Tao; Kane, John M.; Correll, Christoph U.
ABSTRACT: Introduction : Antipsychotic co-treatment is common in schizophrenia, despite lacking evidence for its efficacy and safety. Areas : We conducted a systematic search of PubMed/PsycInfo/CJN/WangFan/CBM without language restrictions from database inception until 05/25/2015 for randomized trials comparing antipsychotic monotherapy with antipsychotic co-treatment in ≥20 adults with schizophrenia reporting meta-analyzable adverse events (AEs) data. Meta-analyzing 67 studies (n=4, 861, duration=10.3±5.2 weeks), antipsychotic co-treatment was similar to monotherapy regarding intolerability-related discontinuation (risk ratio (RR)=0.84, 95% confidence interval (CI)=0.53-1.33, p=0.455). While incidence of ≥1 AE was lower with antipsychotic co-treatment (RR=0.77, 95%CI=0.66-0.90, p=0.001), these results were solely driven by open-label and efficacy-focused studies. Adjunctive D2-antagonists lead to less nausea (RR=0.220, 95%CI=0.06–0.87, p=0.030) and insomnia (RR=0.26, 95%CI=0.08-0.86, p=0.028), but higher prolactin (SMD=2.20, 95%CI=0.43-3.96, p=0.015). Conversely, adjunctive partial D2-agonists (aripiprazole=100%) resulted in lower electrocardiogram abnormalities (RR=0.43, 95%CI=0.25-0.73, p=0.002), constipation (RR=0.45, 95%CI=0.25-0.79, p=0.006), drooling/hypersalivation (RR=0.14, 95%CI=0.07-0.29, p<0.001), prolactin (SMD=-1.77, 95%CI=-2.38, -1.15, p<0.001), total and LDL-cholesterol (SMD=-0.33, 95%CI=-0.55, -0.11, p=0.003; SMD=-0.33, 95%CI=-0.54, -0.10, p=0.004). Expert opinion : No double-blind evidence for altered AE burden associated with antipsychotic co-treatment was found. However, AEs were insufficiently and incompletely reported and follow-up duration was modest. Adjunctive partial D2-agonists might be beneficial for counteracting several AEs. High-quality, long-term studies that comprehensively assess AEs are needed.